The Expression of Matrix Metalloproteinases in Eyes with Intraocular Lymphoma. (17th November 2022) - Fukutsu, Kanae; Kase, Satoru; Iwata, Daiju; Suzuki, Kayo; Namba, Kenichi; Ishida, Susumu
ABSTRACT: Purpose: The purpose of this study is to investigate matrix metalloproteinases (MMPs) expression in human intraocular lymphoma (IOL). Methods: Two enucleated eyes and seven cell-block samples obtained from patients with IOL who underwent vitrectomy were used. Immunopathological examinations were performed for detection of MMP-2, MMP-9, and TIMP-4 expressions. Results: In the enucleated eye with primary IOL (PIOL), MMP-2 was negative, and MMP-9 and TIMP-4 were positive in the lymphoma cells, while in the enucleated eye with secondary IOL (SIOL), all the molecules were positive. Among the cell-block samples with PIOL, the positive rate in lymphoma cells of MMP-2, MMP-9, and TIMP-4 was 75%, 100%, and 75%, respectively. In the cell-block samples with SIOL, the positive rates of MMP-2, MMP-9, and TIMP-4 were all 100%. Conclusions: MMP-2, MMP-9, and TIMP-4 were expressed in lymphoma cells using the specimens of human IOL, suggesting that MMPs may play an important role in the development of IOL.